2016
DOI: 10.1364/oe.24.014311
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional reflectionless phenomenon in periodic ternary layered material

Abstract: Unidirectional reflectionless phenomenon is reported in periodic ternary layered material (PTLM). The unit of the material is composed of two real dielectric layers and a complex medium (loss or gain) layer. The model is analyzed by coupled mode theory. Because of the asymmetric coupling between the forward and backward propagating modes, the left- and right-side reflectivities of this PTLM are generally unequal. The necessary and sufficient (NS) condition for unidirectional reflectionless phenomenon is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…A particularly interesting case of unidirectional reflectionless transmission is unidirectional invisibility, for which the transmitted wave is identical to that without the local structure [5]. Unidirectional reflectionless transmission has been studied on various PT -symmetric optical structures, including one-dimensional (1D) structures [5,6], planar layered structures [8][9][10][11][12], planar inhomoge- * Corresponding author: ljyuan@ctbu.edu.cn neous structure [13], two-dimensional (2D) closed waveguides [14], and 2D coupled waveguide resonator systems [15]. Experimental demonstrations have been reported for PT -symmetric photonic lattices [16] and microscale SOI waveguides [17].…”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting case of unidirectional reflectionless transmission is unidirectional invisibility, for which the transmitted wave is identical to that without the local structure [5]. Unidirectional reflectionless transmission has been studied on various PT -symmetric optical structures, including one-dimensional (1D) structures [5,6], planar layered structures [8][9][10][11][12], planar inhomoge- * Corresponding author: ljyuan@ctbu.edu.cn neous structure [13], two-dimensional (2D) closed waveguides [14], and 2D coupled waveguide resonator systems [15]. Experimental demonstrations have been reported for PT -symmetric photonic lattices [16] and microscale SOI waveguides [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for nonperiodic non-PT-symmetric systems, which are relatively easy to fabricate and more compact. Although Yang et al demonstrated broadband unidirectional reflectionless light transport at an EP in a periodic ternary-layered structure consisting of lossy and lossless dielectrics [126], large-sized periodic structures are not easy to implement in densely integrated optical chips.…”
Section: ) Smentioning
confidence: 99%
“…In such structures the reflection is zero when measured from one end of the structure at optical exceptional points, and nonzero when measured from the other end. Unidirectional light reflectionlessness can also be attained in non-PT-symmetric structures with unbalanced gain and loss [18][19][20][21][22][23][24][25][26][27][28][29][30]. This is due to the fact that exceptional points exist in a larger family of non-Hermitian Hamiltonians [18].…”
Section: Introductionmentioning
confidence: 99%